Murder at Arleigh [large type] - Maxwell, Alyssa (Maxwell, Alyssa. Gilded Newport mystery, 2025)
"April 1903: Emma and Derrick Andrews have been invited to the wedding of her cousin Reggie Vanderbilt and heiress Cathleen Neilson at the Bellevue Mansion, Arleigh. Their hosts are a popular young couple who are leasing the home for the summer -- Harry and Elizabeth "Bessie" Lehr. Known for his practical jokes, Harry is the toast of parties, earning a reputation as the court jester of the Gilded Age. However, as Emma soon learns, behind closed doors he is dead serious. Following the wedding, Bessie comes to Emma for help, insisting that her husband is cruel to her in private, telling her outright he married her only for her money and finds her repulsive. Divorce is unthinkable. Now she believes he is plotting to murder her and make it look like an accident: a broken balcony railing she might have leaned on, a loose stair runner that could have sent her tumbling down a staircase, faulty brakes in the car she uses . . . Some would say being trapped in a loveless marriage is a fate worse than death. Not Bessie-she wants to live! Unsure if these situations are mere coincidences or add up to premeditated sabotage, Emma agrees to investigate and determine if Newport's merry prankster is engaged in a cold-blooded game of life or death . . ."--